Moving towards pathogen‐specific T cells post‐stem cell transplant as standard of care. (April 2015) - Blyth, E.; Clancy, L.; Gottlieb, D.
<x xml:space="preserve">Abstract</x> Infection remains a large contributor to mortality post‐allogeneic haemopoietic stem cell transplantation (HSCT). Non‐bacterial pathogens cause disease post‐HSCT due to impaired cellular immunity that persists for months to years. Treatment with antiviral or antifungal pharmacotherapy is problematic due to drug toxicity, treatment failure and high cost. Pathogen‐specific T cells (PSTs) from transplant donors provide a potential solution to the problem of impaired recipient immunity by directly and rapidly reconstituting immunity, thereby preventing or controlling infections. A number of phases I and II clinical trials of PSTs that have focused primarily on cytomegalovirus, Epstein–Barr virus and adenovirus have now been performed in the prophylactic, pre‐emptive and treatment settings. These trials show that transferred cells are safe and that they expand in vivo, respond to viral antigens and can prevent or control disease. At the current time, manufacture remains the domain of large centres with the necessary expertise and infrastructure, but automation and standardization will allow techniques to be more widely adopted. It is clear that adoptive T cell transfer will form part of the future of transplantation, with the current challenge being to perform large randomized clinical trials demonstrating safety and efficacy to justify the investment in infrastructure required for widespread incorporation of this therapy into routine clinical practice.